The influence of patient-perceived service quality and brand trust on word of mouth / Efendi and Maria Elizabeth - Efendi, Efendi; Elizabeth, Maria (Universiti Teknologi MARA Cawangan Sarawak, 2017)
The health care service providers such as the hospitals are facing the challenges of gaining customer loyalty. Health care service is a high involvement and high risk service. Therefore, brand trust can play an important role in influencing customer loyalty and word of mouth. This empirical research was conducted to find out the influence of service quality on brand trust and word of mouth in a private hospital. The data were collected using a six-item Likert scale with closed questions. The dimensions of service quality are reliability, assurance, tangibility, empathy, and responsiveness. Questionnaires were distributed using stratified random sampling to 215 respondents who have had in-patient care in a private hospital in Jakarta, St. Carolus Hospital. They were chosen because they would have a more intensive interaction with the service provider and the facility during their treatment. The sampling technique used is stratified random sampling method. The data were analyzed using the Structural Equation Modeling (LISREL). The result showed that brand trust mediated the influence of service quality on word of mouth. The ability of a hospital to build trust among its customers can influence its future performance through positive word of mouth.